2019
DOI: 10.1007/s40617-019-00368-z
|View full text |Cite
|
Sign up to set email alerts
|

The Training Experiences of Behavior Analysts: Compassionate Care and Therapeutic Relationships with Caregivers

Abstract: Successfully working with families of children with autism requires technical behavior-analytic skills and critical interpersonal relationship-building skills. Taylor, LeBlanc, and Nosik (2018) suggested that many Board Certified Behavior Analysts might have been trained in graduate programs that focus primarily on conceptual and technical skills with little coverage of skills related to building therapeutic relationships. The current paper provides the results of an online survey of the precredential and post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(31 citation statements)
references
References 20 publications
0
30
0
1
Order By: Relevance
“…Families may need assistance to ensure that their basic needs are met, including food, shelter, clothing, safety, healthcare, and financial support, before behavior analysts provide other kinds of support. Practitioners will need more than their standard toolbox of behavioral parenting strategies: technical skills must be balanced with fluency in collaboration, compassionate care, therapeutic alliance and self-care skills (LeBlanc, Taylor, & Marchese, 2019;Taylor, LeBlanc, & Nosik, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Families may need assistance to ensure that their basic needs are met, including food, shelter, clothing, safety, healthcare, and financial support, before behavior analysts provide other kinds of support. Practitioners will need more than their standard toolbox of behavioral parenting strategies: technical skills must be balanced with fluency in collaboration, compassionate care, therapeutic alliance and self-care skills (LeBlanc, Taylor, & Marchese, 2019;Taylor, LeBlanc, & Nosik, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Families may need assistance to ensure that their basic needs are met, including food, shelter, clothing, safety, health care, and financial support, before behavior analysts provide other kinds of support. Practitioners will need more than their standard toolbox of behavioral parenting strategies: Technical skills must be balanced with fluency in collaboration, compassionate care, therapeutic alliance, and self-care skills (LeBlanc, Taylor, & Marchese, 2019;Taylor, LeBlanc, & Nosik, 2019).…”
mentioning
confidence: 99%
“…In the past few years, some behavior analysts have suggested that in addition to learning the conceptual and technical aspects of ABA, behavior analysts need to focus on compassionate care-the soft skills that will help them work more successfully with families, clients, and other consumers (e.g., Taylor et al, 2019). Core components of compassionate care include active listening, collaboration, understanding a family's culture, avoiding jargon, and asking open-ended questions (LeBlanc et al, 2019).…”
Section: Learn and Practice The "Soft Skills"mentioning
confidence: 99%